DINAMIKA METAFORA HUMAN DALAM PUISI SYAJARAH AL-ZAITŪN AL-SĀNIYAH KARYA MAHMOUD DARWISH: KAJIAN SEMANTIK KOGNITIF - Kisti Arilla (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2026)
Background: In Palestinian literature, the olive tree symbolizes identity, memory, and resistance. However, the role of human metaphors as a cognitive strategy of rehumanization in Mahmoud Darwish's Syajarah al-Zaitūn al-Sāniyah remains underexplored.. Purpose: This study investigates how human metaphors construct rehumanization through a cognitive semantic perspective. Method: Using a descriptive qualitative approach, this study analyzes metaphorical expressions in the poem based on Michael C. Haley's metaphor hierarchy through cognitive mapping and thematic interpretation. Results: Seven human metaphors were identified, portraying the olive tree as an entity with emotional, social, ethical, and moral agency. These metaphors form a coherent cognitive structure that represents steadfastness, historical legitimacy, and dignified resistance against colonial dehumanization Conclusion: Human metaphors function not merely as literary devices but as a cognitive strategy of rehumanization, contributing to cognitive semantic studies and modern Arabic resistance literature. Keywords: Human Metaphor, Syajarah al-Zaitūn al-Sāniyah, Mahmoud Darwish, cognitive semantics, Rehumanization.